Integration of Religious and Social Values in the Development of the Indonesian Constitution Era 5.0 - Rodiah Nur, Efa; Mu'in, Fathul (KnE Social Sciences, 2024)
This study examines the inclusion of Islamic religious and social values in the development of the constitution in Indonesia because it is undeniable that the role of religion brought by the Prophet Muhammad is an inspiration for making laws in the country. The social values of the community or what is referred to as customary law are also integrated into positive law or the Indonesian constitution. This research uses a socio-legal approach. This study concludes that religious and social values of society enter National Law through adjustment to legal values and through system transplantation. The existence of Islamic Law in the Development of National Law identified that the paradigm of Pancasila in which the Islamic legal system is contained and the positivization of Islamic law into national law through several codifications and legal unification has been in the form of laws and regulations. Religious values and community customs are integrated into the constitution of Indonesia, which has the potential to continue to develop along with the times and technology. Keywords: integration, religion, social, constitution